2019
DOI: 10.1155/2019/2642740
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Atherosclerotic Plaque Vulnerability Rather than Stenosis Predisposes to Non-ST Elevation Acute Coronary Syndromes

Abstract: Background. Non-ST elevation acute coronary syndromes (NSTE-ACS) may arise from moderately stenosed atherosclerotic lesions that suddenly undergo transformation to vulnerable plaques complicated by rupture and thrombosis. Objective. Assessment and tissue characterization of the coronary atherosclerotic lesions among NSTE-ACS patients compared to those with stable angina. Methodology. Evaluation of IVUS studies of 312 coronary lesions was done by 2 different experienced IVUS readers, 216 lesions in 66 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…В настоящее время оптимальная медикаментозная терапия остается ключевым методом первичной и вторичной профилактики острых коронарных событий. Реваскуляризация миокарда уменьшает симптомы ишемии и улучшает качество жизни, но не всегда предотвращает развитие ОКС [6,7]. Но, несмотря на проводимую терапию, сохраняется риск неблагоприятного исхода.…”
Section: ключевые словаunclassified
“…В настоящее время оптимальная медикаментозная терапия остается ключевым методом первичной и вторичной профилактики острых коронарных событий. Реваскуляризация миокарда уменьшает симптомы ишемии и улучшает качество жизни, но не всегда предотвращает развитие ОКС [6,7]. Но, несмотря на проводимую терапию, сохраняется риск неблагоприятного исхода.…”
Section: ключевые словаunclassified
“…Indeed, intravascular ultrasound studies have shown that, compared with chronic coronary disease, in acute coronary syndromes, the incidence of unstable features is higher also in non-culprit lesions. [27][28][29] Often, these lesions appear only moderately stenotic at angiography, in part due to positive vessel remodelling. This is consistent with the previous observation, reported over many years, that the extent of luminal narrowing is a poor predictor of subsequent acute events.…”
Section: Complete Trialmentioning
confidence: 99%
“… 11 , 12 , 13 Thus, cardiovascular events are more related to the degree of vulnerability of the coronary plaque than to the severity of coronary stenosis. 14 It would be more appropriate to assess the degree of atherosclerotic plaque instability by optical coherence tomography or coronary intravascular ultrasound instead of assessing the hemodynamic severity of the plaque by visual assessment or FFR, as has been done in most RCTs. Moreover, diffuse coronary spasms are frequently present in the acute phase of STEMI, and this may lead to an overestimation of stenosis severity in nonculprit vessels.…”
mentioning
confidence: 99%